ниже.
Объяснение:
так вроде.
1.
a.4x-y=1
3x+2y=-13
4x=y+1
3x+2y=-13
x=y/4+1/4
3(y/4+1/4)+2y=-13
x=y/4+1/4
(11y)/4+3/4=-13
x=y/4+1/4
(11y)/4=-55/4
x=y/4+1/4
y=-5
x=-1
y=-5
b.4x-y=1
y=4x-1
(0;-1),(1;3)
3x+2y=-13
y=-(3x)/2-13/2
(-1;-5),(-5;1)
по двум точкам.
c.4x-y=1
3x+2y=-13
2(4x-y)+(3x+2y)=2*1-13
11x=-11
x=-1
y=-5
2.гиря - y
гантель - x
2y+3x=47,
3y-6x=18
3x=47-2y
3y-6x=18
x=47/3-(2y)/3
3y-6x=18
x=47/3-(2y)/3
3y-6(47/3-(2y)/3)=18
x=47/3-(2y)/3
7y-94=18
x=47/3-(2y)/3
7y=112
x=47/3-(2y)/3
y=16
x=5
y=16
гантель - 5 кг
гиря - 16 кг
3.
3(2x+y)-26=3x-2y
15-(x-3y)=2x+5
-26+6x+3y=3x-2y
15-x+3y=2x+5
-26+6x+3y=3x-2y
3y=3x-10
-26+6x+3y=3x-2y
y=x-10/3
-26+6x+3(x-10/3)=3x-2(x-10/3)
y=x-10/3
9x-36=x+20/3
y=x-10/3
8x=128/3
y=x-10/3
x=16/3
y=x-10/3
x=16/3
y=2
(x²cosx)'=(uv)' u=x² u'=2xdx v=cosx v'=-sinxdx
(uv)'=u'v+v'u=2xcox-x²sinx
y'=2xcosx-x²sinx-cosx
y'(π)=2πcos(π)-π²sin(π)-cosπ=-2π-0+1=1-2π
y=√3sinx+cosπ/3-3/π*x²
y'=√3cosx+0-6/π*x
y'(π/6)=√3cosπ/6-6/π*π/6=√3*√3/2-1=1.5-1=0.5